Midnight sun [large type] - Nesbø, Jo, 1960- (Random House Large Print, 2016)
Blood on Snow Jon is on the run. He has betrayed Oslo's biggest crime lord: The Fisherman. Fleeing to an isolated corner of Norway, to a mountain town so far north that the sun never sets, Jon hopes to find sanctuary amongst a local religious sect. Hiding out in a shepherd's cabin in the wilderness, all that stands between him and his fate are Lea, a bereaved mother, and her son, Knut. But while Lea provides him with a rifle and Knut brings essential supplies, the midnight sun is slowly driving Jon to insanity. And then he discovers that The Fisherman's men are getting closer...